2017
DOI: 10.1007/s12298-017-0451-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of drought tolerance of soybean plants by using methyl jasmonate

Abstract: Methyl jasmonate (MeJA) is a naturally occurring plant growth regulator and play vital roles in plant defense and many developmental processes such as root growth and seed germination. This study was undertaken to study the possible role of using methyl jasmonate to alleviate the adverse effect of water stress on soybean genotypes (Giza 22 and 35). The results showed that water stress reduced shoot length, fresh and dry weights of shoot and root, photosynthetic pigments, relative water content and oil content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(47 citation statements)
references
References 71 publications
6
41
0
Order By: Relevance
“…This reduction may be due to the pigment photo-oxidation and the degradation of chlorophyll. Similar results are reported in cotton and soybean plants [30,31]. Plants respond to drought stress by closing stomata to limit water loss, reducing carbon flow [36] and reducing ATP synthase and Rubisco activities [37].…”
Section: Changes In Photosynthetic Pigmentssupporting
confidence: 76%
See 1 more Smart Citation
“…This reduction may be due to the pigment photo-oxidation and the degradation of chlorophyll. Similar results are reported in cotton and soybean plants [30,31]. Plants respond to drought stress by closing stomata to limit water loss, reducing carbon flow [36] and reducing ATP synthase and Rubisco activities [37].…”
Section: Changes In Photosynthetic Pigmentssupporting
confidence: 76%
“…Our results showed that moderate and severe drought stress caused a reduction in chickpea growth and yield. Decreases in the growth of common bean plants [27], wheat plant [28] and soybean plants [29][30][31] have been recorded as a result of drought stress. A decline in plant growth due to drought stress may be attributed to the deregulation of elongating cells due to disruption of the flow of water from the xylem to elongating cells, reduction in the growth-promoting hormones, cell elongation, cell expansion and mitosis during cell division [32].…”
Section: Changes In Yield Attributementioning
confidence: 99%
“…Conversely, the exogenous application of JAs could alleviate drought stress associated damage in P. armeniaca. Foliar application of MeJA on soybean leaves can enhance water stress tolerance capacity, and further analysis showed increased levels of sugars, phenolic compounds, and flavonoids [35]. Such findings indicate that both endogenous and exogenous JAs participate in drought stress tolerance in plants.…”
Section: Drought Stressmentioning
confidence: 74%
“…The increase in the endogenous JA content was rapid and transient in A. thaliana [21] and citrus (Citrus paradisi × Poncirus trifoliata) [115] immediately after drought stress, but the content decreased to the basal level with prolongation of the stress. MeJA treatment could improve the drought resistance in peanut (Arachis hypogaea) [116], rice (Oryza sativa) [117], soybean (Glycine max) [118], and broccoli (Brassica oleracea) plants [119]. The application of exogenous MeJA not only increased the total carbohydrate, polysaccharide, total soluble sugar, free amino acid, total proline, and protein contents, but also the activities of catalase (CAT), POD, and SOD in maize plants (Zea mays) [120].…”
Section: Jasmonic Acid Signaling Under Drought Stressmentioning
confidence: 99%